Influencia del medio de comunicación virtual en la enseñanza académica de los estudiantes de la Unidad Educativa Manabí del cantón Pichincha, año 2019 - Marcillo de la Cruz, Genesis Beatriz (2020)
The new information technologies, communication offers a diversity of means and resources to contribute to teaching, however, it is not the available technology that determines the models, procedures, or didactic strategies. The creation of virtual learning environments inspires the best pedagogy theories as a learning tool. The use of virtual media as educational technological tools are of great help because of its accessibility in any technical or scientific area, it promotes competitive and efficient learning, highlighting that it is innovated with an inclusive, motivating and meaningful process, since change is made most common to the use of a multimedia, interactive, and application language using different synchronous activities: chats, video conferences, and asynchronous activities: blogs, concept maps and online timelines. Profit, benefit, interest gain. The virtual media are also present in the educational institutions of Ecuador, becoming an aid of tools and advances in technology and communication, one of the fields that is taking advantage of is education, since the internet is an Effective means to ensure communication, interaction, and sending information.